Liver Injury Induced by Anticancer Chemotherapy and Radiation Therapy - Y. Maor; S. Malnick (International Journal of Hepatology)
Cytotoxic chemotherapy prolongs survival of patients with advanced and metastatic tumors. This is, however, a double-edged sword with many adverse effects. Since the liver has a rich blood supply and plays an active role in the metabolism of medications, it is not surprising that there can be hepatic injury related to chemotherapy. In addition, radioembolization may affect the parenchyma of normal and cirrhotic livers. We review chemotherapy-associated liver injury in patients with colorectal liver metastases, including downsizing chemotherapy and neoadjuvant chemotherapy. We discuss the mechanism of the hepatic injury, secondary to reactive oxygen species, and the spectrum of hepatic injury including, steatosis, steatohepatitis, hepatic sinusoidal injury and highlight the pharmacogenomics of such liver insults. Methods for reducing and treating the hepatotoxicity are discussed for specific agents including tamxifen and the newly introduced targeted antibodies.